BUDAYA PENJARA, SUBKULTUR TERORISME DAN RADIKALISASI: PERSPEKTIF KRIMINOLOGI BUDAYA - Arham, Laode (UI Scholars Hub, 2020)
This paper aims to explain how the radicalization of prisoners in correctional institutions (Lapas) occurs through the perspective of Cultural Criminology. Radicalization takes place through a lifestyle and subculture of terrorist prisoners which is supported by the culture and the actual prison system which is the result of the interaction and agreement of the actors. All of the cultural aspects that shape radicalization are part of a unique prison culture, as the subculture of terrorism. By using qualitative methods, research data were collected through observation, interviews and the author's experience in interacting with various actors in several prisons. This paper will explain the theoretical framework of cultural criminology and prison culture, then describe the symbolic, cultural and identity aspects of terrorist prisoners whose own subcultures in prison culture. Analysis of cultural criminology shows that the subculture of convict terrorist (terrorism) provides a lifestyle that defines them as militant organizations, networking and building a “prison gangs”; also support them with an